AVALIAÇÃO DE PINUS ELLIOTTII (ENGELM.) COM CINCO DIFERENTES IDADES NO MUNICÍPIO DE IJUÍ – RS - Filho, Ângelo C.; Brum, José; Krüger, Cleusa A. M. B.; Schirmer, Jorge; Lucchese, Osório A. (Salão do Conhecimento, 2013)
Resumo